2022
DOI: 10.3390/gels8040232
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Cancer Therapy via pH-Functionalized Nanoparticles: A Scoping Review of Methods and Outcomes

Abstract: (1) Background: In recent years, several studies have described various and heterogenous methods to sensitize nanoparticles (NPs) to pH changes; therefore, in this current scoping review, we aimed to map current protocols for pH functionalization of NPs and analyze the outcomes of drug-loaded pH-functionalized NPs (pH-NPs) when delivered in vivo in tumoral tissue. (2) Methods: A systematic search of the PubMed database was performed for all published studies relating to in vivo models of anti-tumor drug delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 150 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…These drug release data agree well with the vesicle degradation results ( Figure 4 b), where the vesicle size drastically decreased to 63 ± 23 nm after 12 h of incubation at pH = 3. These DOX release results also confirm that the vesicle degradation mainly occurs in the pH range from 4 to 3, which is characteristic of ester bond degradation ( Figure 4 b and Figure 5 a) [ 53 ].…”
Section: Resultssupporting
confidence: 67%
“…These drug release data agree well with the vesicle degradation results ( Figure 4 b), where the vesicle size drastically decreased to 63 ± 23 nm after 12 h of incubation at pH = 3. These DOX release results also confirm that the vesicle degradation mainly occurs in the pH range from 4 to 3, which is characteristic of ester bond degradation ( Figure 4 b and Figure 5 a) [ 53 ].…”
Section: Resultssupporting
confidence: 67%
“…( 91 , 92 ). It has recently been summarized that several types of pH-sensitive nanoparticle conjugates with paclitaxel, doxorubicin, or others enhance drug delivery and potentiate anticancer effects in various experimental cancer cell lines ( 93 ).…”
Section: Tumor Acidity As a Target Of Treatmentmentioning
confidence: 99%
“…According to Ref. [ 78 ], 45.8% of published-by-now articles consider polymers to be a material for the fabrication of pH-responsive targeted delivery systems, 10% consider lipids, 12.5% consider mesoporous silica, and 6.7% consider metals ( Figure 3 ). However, current challenges push researchers to create hybrid carriers that combine properties of different materials; thus, the DDSs developed over the last 5 years are mostly multicomponent capsules or particles comprising inorganic compounds and specific polymers which endow them with multifunctionality.…”
Section: Principles Of Ph-responsive Drug Deliverymentioning
confidence: 99%
“…Metal nanoparticles were the fourth most frequently used class of carriers among pH-responsive DDSs in the last 5 years [ 78 ]. Studies have shown that metal oxide nanoparticles (such as zinc oxide) exhibit high cancer cell selectivity, drug retention, and controlled release.…”
Section: In Vivo Studies Of Ph-responsive Ddssmentioning
confidence: 99%